The diversity of systemic innovation thinking: The theoretical underpinnings of NIS and IMP and the different assessment of an industry. Issue 1 (13th April 2015) - Eklund, Magnus; Waluszewski, Alexandra
Abstract : Purpose: – The purpose of this paper is to analyze the different assessments of a particular industry and its ability to innovative, renew and prosper, but also to look into the underlying assumptions that are hiding behind the systemic approaches utilized in these assessments. The point of departure is an empirical puzzle: one group of studies presents a rather optimistic view of the Swedish life science industry and its ability to economize on research, policy and industrial investments. Another group of studies presents much a darker view, questioning the capacity of new companies to reach economic endurance, as well as the possibility of keeping the actually successful companies within the country. At a first sight it appears as if the two groups of studies are resting on a common theoretical ground: all seem to depart from a systemic innovation perspective that challenges the idea of an independent business landscape. Design/methodology/approach: – The difference between the assessments becomes comprehensible once the authors allow for a variety of systemic approaches in innovation thinking. The authors propose an ideal-typical distinction between two types of system perspectives; those that view technology as entangled in its environment and those that view technology as disentangled from its environment. The authors use the national innovation system (NIS) and the industrial network (IMP) approaches to exemplify the two perspectives. Findings: – An implication of the study is that the term "systemic perspective" is very broad and encompassing, something that in turn points to the importance of being clear about what the authors mean with a system, but also with what the theoretical assumptions focus on and abstract away from. Originality/value: – The ideal-typical distinction between two types of system perspectives; those that view technology as entangled in its environment and those that view technology as disentangled from its environment. The authors use the NIS and the IMP approaches to exemplify the two perspectives.